Synthesis, CharacterizationandAntibacterial Studyof NewSulfa Drug Derivatives Containing 4-Thaiazoliodinones - Monther Faisal Mahdi; Ali Hussein Alwan; Shahlaa Zuhair Abdul-Majeed (College of Pharmacy / Mustansiriyah University, 2018)
New series of sulfamethoxazole containing -4-thiazolidinone ring (compounds IV(a-f)) have been synthesized and evaluated for their antibacterial activity against gram positive bacteria & gram negative bacteria. These compounds expected to have higher antibacterial activity than sulfamethoxazole, due to the presence of 4-thiazolidinone pharmacophore. The purity of the synthesized compounds was detected by determination of physical properties (melting points &Rf values). The chemical structure of the intermediate and final compounds was characterized and confirmed by measuring FT-IR spectroscopy, elemental microanalysis (CHNS) and 1H-Nuclear magnetic resonance (1H-NMR) spectroscopy. The preliminary study of antimicrobial activity of the final compounds were evaluated by well diffusion method. All tested compounds exert significant antibacterial activity against gram positive bacteria and gram negative bacteria especially Escherichia coli, Klebsiellapneumoniae, Staphylococcus aureus and Streptococcus pyougenes, which compared to DMSO as control, and sulfamethoxazole as standard. In comparison of the antibacterial activity results among the tested compounds, the results showed that compound (IVf) may regard the best one and compound (IVc) the lower one. These results encourage further evaluation of these compounds for different antimicrobial activities.